HER2-Positive Breast Cancer: A Literature Review - Adidaifa, Muhammad Fikri (Jurnal Biologi Tropis, 2025)
Breast cancer remains a malignancy with high global mortality rates. Approximately 15-20% of these cases are Human Epidermal Growth Factor Receptor 2 (HER2) positive subtype, characterized by aggressiveness, high risk of metastasis, and poor prognosis if left untreated. This literature review aims to discuss the pathophysiology, diagnostic methods, and recent advancements in the management of HER2-positive breast cancer. The study utilized a literature review method, sourcing data from PubMed, Google Scholar, and ScienceDirect databases. A total of 23 literatures published within the last 5-10 years were selected based on inclusion criteria. Overexpression of HER2 protein triggers the activation of MAPK and PI3K/AKT/mTOR signaling pathways, stimulating uncontrolled cell proliferation. Diagnosis is established via Immunohistochemistry (IHC) and confirmed by In Situ Hybridization (ISH) following ASCO/CAP 2018 guidelines. Current management shows a significant shift; neoadjuvant and first-line advanced stage therapies prioritize dual blockade (Trastuzumab and Pertuzumab). Furthermore, the new generation Antibody-Drug Conjugate (ADC), Trastuzumab Deruxtecan (T-DXd), has demonstrated superior efficacy compared to T-DM1 as a second-line therapy. Comprehensive understanding of HER2 molecular biology and advances in targeted therapy have transformed the clinical landscape, increasing survival rates and significantly improving the prognosis of HER2-positive breast cancer patients.